Age and cohort trends in disability among Chinese older adults - Pan, Chaoping; Cao, Na; Kelifa, Mohammedhamid Osman; Luo, Shuren (Frontiers in Public Health, 2023)
Objective This study aimed to examine age and cohort trends in disability among Chinese older adults and explore the disablement process factors that may explain the cohort trends in disability. Methods This study used data from five waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS). A hierarchical logistic growth model was used to analyze the A–P–C effects and the contributors of cohort trends. Results ADL, IADL, and FL among Chinese older adults showed increasing age and cohort trends. FL was more likely to result in IADL disability than ADL disability. Among the disablement process factors, gender, residence, education, health behavior, disease, and family income contributed to most of the cohort trends in disability. Conclusions As older adults face increasing disability trends, it is necessary to distinguish age and cohort trends and develop more effective interventions according to relative contributors to prevent disability among them.